PADDY FIELD CONVERSION IN INDONESIA IN A CONTEMPORARY GEOGRAPHIC PERSPECTIVE: A CONCEPTUAL OVERVIEW OF HUMAN-NATURE DIALECTICS (JURNAL GEOGRAFI, 2021)
Experts from various perspectives have widely reviewed the patterns, processes, reasons, and impacts of paddy field conversion. However, most of these reviews tend to understand paddy fields from the physical-material dimension. By using the perspective of contemporary geography, this paper provides a critical conceptual overview of the conversion of paddy fields through the elaboration of human-nature dialectic as a central theme in the discipline of geography. The dialectic also contains identity, spatial awareness, and spatial-symbolic order issues that affect the existence of farmers and their paddy fields. This critical review results in the argument that the relationship between farmers and paddy fields represents a spatial-symbolic order that contains values, enthusiasm, identity, and living traditions. The identity and existence of farmers are part of the existence of paddy fields. Paddy fields have become part of the minds and consciousness of the farmers. The conversion of paddy fields will reduce the eco-cultural relations in this order and replace it with a capitalistic system.Keywords: contemporary geography, human-nature dialectic, paddy field conversion, spatial-symbolic order, sustainable agriculture